174k views
1 vote
Helppppppppppppppppppp

Helppppppppppppppppppp-example-1

2 Answers

7 votes

Answer:

x = 3

1. Subtract 5 from both sides of the equation.

6 + 5 = 3 + 1 4 6 + 5 − 5 = 3 + 1 4 − 5

2. Simplify

Subtract the numbers 6 = 3 + 9

3. Subtract 3x from both sides of the equation.

6 = 3 + 9 6 − 3 = 3 + 9 − 3

4. Simplify.

Combine like terms - 3x = 9

5. Divide both sides of the equation by the same term

3 = 9 3 3 = 9 3

6. Simplify

Cancel terms that are in both the numerator and denominator Divide the numbers = 3

User Tio Pepe
by
5.4k points
2 votes
the answer to the problem is
x=3
User Frankie Roberto
by
4.9k points